The literature of misogyny in medieval Spain : the "Arcipreste de Talavera" and the "Spill" - Solomon, Michael (Michael Ray) (Cambridge studies in Latin American and Iberian literature, 1997)
The Literature of Misogyny in Medieval Spain examines the medical underpinnings of two major misogynist works from the fifteenth-century Iberian: Alonso de Martinez's Arcipreste de Talavera and Jacme Roig's Spill. Michael Solomon argues that these works gained their rhetorical force by linking concerns over health and illness with men's behavior toward women. Solomon shows how the demonization of women in medieval society was more than vaguely cultural; it was part of the healing arts, considered vital to the well-being of men.